Analisis Hukum Keabsahan Kontrak Elektronik sebagai Salah Satu Bentuk Kesepakatan Transaksi Elektronik Berdasarkan Perundang-undangan di Indonesia - Fatahillah, Javandalas Nanda Yasser; Sabani, Agil; Najib, Ramanda Faik Hilmi; Rajib, Rayi Kharisma (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The development of information technology has driven significant changes in contracting practices, including the emergence of electronic contracts as a form of agreement in digital transactions. This study aims to analyze the legal basis, validity requirements, constituent elements, and legal status of electronic contracts under the Law of ITE, Government Regulation No. 71 of 2019, Government Regulation No. 80 of 2019, and the general principles of agreement in the Civil Code. The research employs a normative juridical method with a qualitative analytical approach through a literature review of legislation and relevant legal doctrine. The study’s findings indicate that electronic contracts fundamentally possess the same validity as conventional written contracts, provided they satisfy the validity requirements of Article 1320 of the Civil Code and the technical provisions set forth in the implementing regulations of the UU ITE. These provisions include the use of reliable electronic systems, adherence to the principles of prudence and good faith, and the provision of clear electronic information. Electronic contracts must also contain the essentialia, naturalia, and accidentalia elements as regulated in Government Regulation No. 71 of 2019, and they are subject to additional rules applicable to electronic transactions under Government Regulation No. 80 of 2019. The implications of this study underscore the importance of raising electronic system security standards, providing legal education for participants in digital transactions, and strengthening regulations on digital proof and evidentiary rules so that electronic contracts can deliver optimal legal certainty.